Ekstraksi Polifenol Total dari Daun Kadamba (Mitragyna Speciosa Korth.) Menggunakan Malic Acid-Glucose Based Microwave Assisted Extraction - Andi Yusniah; Yuspian Nur; Islamudin Ahmad (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
This study aims to determine the effect of the use of malic acid-glucose based microwave assited extraction (MAE) methods on total polyphenol extraction from kadamba leaves (Mitragyna Speciosa Korth). Samples that have been dried in the extraction using solvents (green solvent) Malic Acid-Glucose with a ratio of 1: 1 and 1: 3 g/g in several conditions including, microwave strength 50% for 10 minutes with a sample ratio and a solvent of 1:10 g/mL. Then the extract solution obtained was measured in total polyphenol levels using the folin ciocalteu (FC) reagent and the absorbance was measured at a wavelength of 791 nm using a UV-vis spectrophotometer. Based on the results of the study obtained levels of polyphenols from each condition of the solvent used is 258mg GAE/g sample (1:1 g/g solvent) and 292mg GAE /g sample (1: 3 g / g solvent). From this study it can be concluded that the method of malic acid-glucose based microwave assited extraction can be used to extract polyphenol compounds from Kadamba leaves quickly, easily and efficiently.